Report on the Review of Labelling of Genetically Modified (GM) Foods (Canberra, 2003)
Contiene: Terms of reference for the review -- Consultattion for the review -- Backround -- Labelling of GM Foods in Australia and New Zealand -- Government implementation of the labelling requirements for GM Foods -- Compliance with and enforcement of the labelling requirements for GM foods -- Labelling GM Foods: International perspectives -- Consumer attitudes to GM Foods and labelling -- The development of a Codex Standard for the labelling of GM foods -- Appendix A. Consultation questions for the review of labelling of GM foods and list of identified stakeholders. Appendix B. Summary of submissions to the review of labelling of GM Foods. Appendix C. Aproved GM Food varieties. Appendix D. Standard 1.5.2 - Food produced using Gene technology. Appendix E. International comparision analysis- regulatory outcomes for the labelling of GM Food. Appendix F. Consumer attitude matrix. Appendix G. The development of a Codex Standard for the labelling of GM Foods summary of developments
Keywords: ALIMENTOS; MEJORAMIENTO GENETICO; ETIQUETADO